Zvýšenie životnosti výsevnej sekcie - Bernát, Rastislav; Záležák, Zoltán; Urminský, Marek; Cebo, Stanislav; Luptaková, Natalia; Urbanovčová, Oľga (Univerzita Pardubice, 2012)
Nowadays the development of technology focuses on the use in a agricultural systems that protect not only natural resources but also promoting its a natural regulatory mechanisms. Designed and technically innovations of agricultural techniques are presented as the most advanced technology and a highest performance technique with unlimited possibilities to purchase from all over the world. In this paper we outlined the innovative changes of a construction seeding mechanism system for increase the lifetime of the individual parts of given device as well as ensured extension of the lifetime of the seeding and a faultless device.
The increasing the lifetime of a seeding section
Keywords: faultless device; extend service life; seed drill; innovation of seeding section